2011
DOI: 10.1080/00319104.2010.483530
|View full text |Cite
|
Sign up to set email alerts
|

Study of electrical transport properties of liquid semiconductor binary alloys using pseudopotential theory

Abstract: To cite this article: Aditya M. Vora (2011) Study of electrical transport properties of liquid semiconductor binary alloys using pseudopotential theory,The electrical transport properties, namely, the electrical resistivity (), the thermoelectric power and thermal conductivity () of several polyvalent semiconductor binary alloys, namely, Cd 1 À X Sn X , Cd 1 À X Pb X and Cd 1 À X Bi X were calculated from the pseudopotential form factors and Percus-Yevick (PY) hard sphere structure factors of Ashcroft and Lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The FZ model is used for calculating the electrical resistivity of Bi-Ga alloy [1][2][3][4][5][6][7][8],…”
Section: Theoretical Basismentioning
confidence: 99%
See 1 more Smart Citation
“…The FZ model is used for calculating the electrical resistivity of Bi-Ga alloy [1][2][3][4][5][6][7][8],…”
Section: Theoretical Basismentioning
confidence: 99%
“…The properties of electronic materials and interfaces between electronic materials are used to elucidate behavior of a variety of semiconductor devices, namely: solid-state lasers, light emitting diodes, bipolar transistors, sensors and field effect transistors etc. Therefore, to understand the electronic structure of the semiconductor materials, the electronic transport properties play an important role and show fascinating interest for research community [1][2][3][4][5][6][7][8]. The electronic transport properties of liquids can be extensively described by the simple model suggested by Faber and Ziman (FZ) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Now assuming the free-electron distribution, an expression for the electrical resistivity of liquid metal in terms of the average of the product of the structure factor and pseudopotential matrix element can be written as, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]21] …”
Section: Computational Methodologymentioning
confidence: 99%
“…And hence the study of electrical transport properties of liquid metals and their alloys remain one of the favourite quantities either experimentally or theoretically. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] It was found that the electrical resistivities of the alloys obey two rules: (i) Nordheim's rule [19] and (ii) Linde's rule. [20] In the Nordheim's rule the resistivity of liquid alloys depends directly on the product of the atomic concentrations in the percentage of the guest and host elements.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, much attention has been paid to the research of liquid-liquid structure transition (L-LST) and resistivity of liquids. [6][7][8][9][10][11] Considerable investigations reveal or indicate the existence of the L-LSTs with reversible or irreversible characters in many liquid metals and alloys. [12][13][14][15][16] Many researchers focus on the microstructure and properties of lead-free solder; however, little attention has been paid to the liquid properties of lead-free solder.…”
Section: Introductionmentioning
confidence: 99%